Food security in the high North contemporary challenges across the circumpolar region - Hossain, Kamrul; Nilsson, Lena Maria; Herrmann, Thora Martina, 1977- (Routledge research in polar regions., 2021)
This book explores the challenges facing food security, sustainability, sovereignty, and supply chains in the Arctic, with a specific focus on Indigenous Peoples. Offering multidisciplinary insights with a particular focus on populations in the European High North region, the book highlights the importance of accessible and sustainable traditional foods for the dietary needs of local and Indigenous Peoples. It focuses on foods and natural products that are unique to this region and considers how they play a significant role towards food security and sovereignty. The book captures the tremendous complexity facing populations here as they strive to maintain sustainable food systems - both subsistent and commercial - and regain sovereignty over traditional food production policies. A range of issues are explored from food contamination risks, due to increasing human activities in the region, such as mining, to changing livelihoods and gender roles in the maintenance of traditional food security and sovereignty. The book also considers processing methods that combine indigenous and traditional knowledge to convert the traditional foods, which are harvested or hunted, into local foods. This book offers a broader understanding of food security and sovereignty, and will be of interest to academics, scholars, and policy makers working in food studies, geography and environmental studies, agricultural studies, sociology, anthropology, political science, health studies, and biology.